Entre conservation et développement : les évolutions récentes de la politique européenne des pêches dans les régions ultrapériphériques de la Caraïbe - Pierre Angelelli (Études Caribéennes)
The European Union currently operates the second reform of its Common Fisheries Policy since its creation in 1970. Established to develop the fisheries and provide incomes for fishermen, the Common Fisheries Policy (CFP) was directed gradually towards the protection of the species and the marine environment. To do this, it sacrificed a large part of the productive sector, but failed, and with the decline of fisheries in Europe, the outermost regions of the Caribbean gained relative importance in this field. They now account for nearly 30% of the national fleet and the Malthusians bases of the CFP are not suited any more to their characteristics: fisheries resources, economic development, jobs, security of food supply, etc. The ongoing reform, which should be in force before 2012, may offer an alternative to the outermost regions of the Caribbean for the implementation of specific measures under Article 349 of the Treaty on the Functioning of the European Union.